2012
DOI: 10.1007/s11250-012-0237-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growing pigs fed diets based on by-products of maize and wheat processing

Abstract: Forty-eight crossbred Landrace × Large white pigs with an average body weight of 8.5 ± 0.4 kg and aged 2 months were used to evaluate performance and carcass characteristics of pigs fed two diets in which bran from maize or wheat was used as the energy source. A third diet based on whole maize grain was used as a control. Animals in groups of four, balanced for litter, sex and weight were allotted to dietary treatments in a completely randomised design with four replications. Data were collected on feed intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Wang et al (2016) demonstrated that high residual oil in diets negatively impacts nutrient digestion and absorption, which was apparent in this study with pigs fed diets that contained high levels of ANC. The higher bre digestibility observed for pigs fed diets containing higher levels of ANC (Table 7) could have resulted from fermentation of the bre in the hind gut with the volatile fatty acids (VFAs) produced, contributing to the net energy requirements of the pigs (Mwesigwa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2016) demonstrated that high residual oil in diets negatively impacts nutrient digestion and absorption, which was apparent in this study with pigs fed diets that contained high levels of ANC. The higher bre digestibility observed for pigs fed diets containing higher levels of ANC (Table 7) could have resulted from fermentation of the bre in the hind gut with the volatile fatty acids (VFAs) produced, contributing to the net energy requirements of the pigs (Mwesigwa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mwesigwa et al [20] stated that feed sources helped influence feed intake. Total feed intake can also be influenced by the concentration of energy, palatability, nutritional content, breed and growth rate [21][22][23].…”
Section: Intake and Digestibility Of Dry Mattermentioning
confidence: 99%
“…The achievement of study was in line with [34] Rideout et al, (2008) stated that source of starch may influence digestibility of mineral Ca and P in growing pigs at 30 kg body weight. Mineral Ca absorption was affected by the balance of Ca and P in the diet [21,34].…”
Section: Mineral Intake and Retention Of Ca And P In The Growing Pigsmentioning
confidence: 99%
“…The by-products of taro cultivation are leaves, petioles, and peel (a waste discarded from taro planting by farmers and taro processing factories). The above by-products are good energy sources for livestock, and with the appropriate preservation practices, these by-products could be beneficial to the livestock farming community and relieve the pressure of competition for food between humans and animals (Mwesigwa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%